A study on the structural, electronic and optical properties of the α-AlF3 compound. (November 2016) - Navarro, J.L.; Albanesi, E.A.; Vidal, R.; Ferrón, J.
Abstract : Graphical abstract: Abstract : Highlights: Ab initio and experimental study on the different properties of the AlF3 bulk. Many-body effects included in the theoretical approach through GW and BSE formalism Very good agreement between theoretical and experimental band-gap and EELS spectra. Abstract: The structural, electronic and optical properties of the insulator α-AlF3 are investigated by first principles calculations using density functional theory, and the band gap and optical response is measured. Our calculations use the generalized gradient approximation for the exchange and correlation potential, within a pseudopotential scheme. In order to improve the ground state formulation for the electronic and optical properties, we included many body effects through the GW approximation for the band gap and the Bethe–Salpeter equation for the excitonic effects in the optical calculations. We contrast our calculations with experiments, by combining Ultraviolet and X-ray photoelectron spectroscopies on AlF3 films grown over Cu(100) to determine the electronic structure, and electron energy loss spectra (EELS) to compare the optical spectra. The density of states shows the important role of F-p states in the bonding, and the band structure reveals the direct band gap at the Γ point of the material, with a value of 10.81 eV obtained within the GW approximation, in very good agreement with the experimental value of 10 eV. We also calculated the imaginary ɛ 2 ( ω ) and real ɛ 1 ( ω ) parts of the dielectric function, the refractive index, the extinction coefficient, the reflectivity at normal incidence, and the electron energy loss spectrum which is in reasonable agreement with the experimental curve, obtaining the main peak in the region about 25 eV. With the Bethe–Salpeter equation we calculated the energy loss spectra of the low energy region above the band gap, where we found excitonic effects that explain the observed experimental peak in this region.